(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The analysis of theater as a cultural fact has experienced numerous controversies throughout the ages. This article makes a panoramic approach to these theoretical proposals, encompassing in the study very different and confronted visions that have taken place for centuries. The fundamental proposals and theorists that have fueled this dispute are presented throughout the work, which in turn serves as an overview of the directions along which theater has taken over the centuries. Far from bringing positions together and as seen in the article, the different theorists and schools have created an increasingly extensive corpus of models fueling a controversy without an outcome.